Cellular and Molecular Mechanisms of Diabetic Atherosclerosis: Herbal Medicines as a Potential Therapeutic Approach. (13th August 2017) - Tian, Jinfan; Liu, Yanfei; Liu, Yue; Chen, Keji; Lyu, Shuzheng
Abstract : An increasing number of patients diagnosed with diabetes mellitus eventually develop severe coronary atherosclerosis disease. Both type 1 and type 2 diabetes mellitus increase the risk of cardiovascular disease associated with atherosclerosis. The cellular and molecular mechanisms affecting the incidence of diabetic atherosclerosis are still unclear, as are appropriate strategies for the prevention and treatment of diabetic atherosclerosis. In this review, we discuss progress in the study of herbs as potential therapeutic agents for diabetic atherosclerosis.